DETERMINAN KEJADIAN ANAK AUTIS BASED ON SYSTEMATIC REVIEW - Rita Dwi Pratiwi; Agus Dwi Pranata; Gita Ayuningtyas; Putri Azzahra (STIKES Pemkab Purworejo, 2023)
Introduction: developmental disorders related to behavior which are generally caused by abnormalities in brain structure or brain function. Autism is a neurological disorder in children that hinders development so they are unable to develop normally. Objective: The aim of this research is to find out whether there are determinants of the incidence of autistic children. Method: the type of research used is descriptive using the Systematic Review method, namely a synthesis of systematic studies that are systematic, clear, comprehensive in identifying, analyzing, evaluating through collecting existing data using an explicit search method and involving a critical review process in study selection. Results: after identifying 10 journals, it was found that there were four factors that influenced autistic children. Conclusion: based on systematic review research, there are seven journals (70%) which state that the incidence of autistic children is influenced by LBW in three journals (30%), father's and mother's age in two journals (20%), family history in two journals (20%), and gender in one journal (10%) Suggestion: it is hoped that this systematic study can increase information and knowledge regarding the determinants of the incidence of autistic children.